2023
DOI: 10.3390/ani13030455
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Autochthonous Strains from the Cecal Content of Creole Roosters for a Potential Use as Probiotics

Abstract: Five strains (CLP2, CLP3, CLP4, CLP5, and CLP6) were isolated from the cecal content of Creole roosters fed without antibiotic growth promoters. Biochemical and morphological tests (negative catalase and oxidase) confirmed the presence of lactic acid bacteria. Additionally, considering the 16s RNA, Lactobacillus vaginalis (CLP2, CLP3, CLP5, and CLP6) and Lactobacillus reuteri (CLP4) were identified. All strains (mainly CLP4 and CLP5) showed variable and significant growth (p < 0.001) at different levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…It is widely acknowledged that infections caused by zoonotic and food−borne enteric pathogens can lead to high morbidity and mortality, ultimately resulting in significant economic losses in the poultry industry [30]. Thus, antimicrobial activity against these pathogens is a major requirement for selecting potential probiotics [5]. In this study, 10 of 44 LAB strains showed broad-spectrum antimicrobial activity against the four pathogens tested (Figure 2A).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…It is widely acknowledged that infections caused by zoonotic and food−borne enteric pathogens can lead to high morbidity and mortality, ultimately resulting in significant economic losses in the poultry industry [30]. Thus, antimicrobial activity against these pathogens is a major requirement for selecting potential probiotics [5]. In this study, 10 of 44 LAB strains showed broad-spectrum antimicrobial activity against the four pathogens tested (Figure 2A).…”
Section: Discussionmentioning
confidence: 69%
“…194, enforced a ban on commercial feed containing growth-promoting drug additives (except for Chinese herbal medicines), effective from 1 July 2020 [3]. However, the use of subtherapeutic antibiotics in the breeding industry is still permitted in some countries, like China, to combat bacterial diseases, which can provoke greater bacterial resistance [4,5]. As a result, researchers have been exploring safe, cost-effective, and efficient alternatives to ensure the long-term sustainability of the livestock and poultry industry [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations